Analysis of the Influencing Factors of Stress in Job: A Research Study in NGOs, INGOs of Birendranagar, Surkhet - Yashoda Thapa (Journal of Nepalese Management and Research, 2024)
This research finds out how stress impacts the employee performance of NGOs and INGOs residing in Birendranagar municipality, Surkhet. The study aimed to investigate how time pressure, workload, lack of motivation, and role ambiguity influenced the performance of the employees. The positivist philosophy was used to complete the research because it permits the creation of hypotheses based on theories. A causal-comparative research design was employed to ascertain the causal relationship between a few chosen inquiry constructs. A survey study was conducted using a structured questionnaire to gather primary data. Four factors were the lack of motivation, with employee performance being the dependent variable and the independent variables being time pressure, workload, lack of motivation, and role ambiguity. The overall findings of the research from the results of multiple regression analysis revealed that time pressure, lack of motivation, and role ambiguity were confirmed to impact employee performance significantly. On the other hand, workload has not considerably affected employee performance.